Implementation of Work Based Learning on Welding Engineering Expertise Competency in The Manufacturing Industry - Achmad Romadin; Didik Nuhadi; Yoto Yoto (Universitas Ahmad Dahlan, 2022)
Vocational High School is an institution that produces labor. However, the problem is that it is actually the highest contributor to unemployment in working-age population value. One of the breakthroughs to anticipate this is by implementing innovative learning. Work Based Learning is a job-oriented learning in industry. This research used qualitative research. The focus of this research is the implementation of Work Based Learning based on the alignment of existing learning in schools with industry, which is arranged in an industrial class implemented curriculum. From the results of the research, there are 3 implementations of Work Based Learning which are integrated with each other including learning in the school environment, in the society, and in the industrial environment. The evaluation of Work Based Learning was carried out by means of daily test assessment, mid-test assessment, final test assessment, skill competency test and open examination of industrial work practice report